Społeczno-ekonomiczne determinanty zapotrzebowania na usługi pocztowo- telekomunikacyjne - Adamski, Eugeniusz; Karpiński, Zdzisław (Wydział Prawa i Administracji UAM, 1971)
The purpose of the article is to show the connection between postaltelecommunication services and socio-economic factors forming the numerical and qualatative level of these services. The problem was reduced to an example of iundamental services of postal- -telecommunications as representatives of communication services and socio-economic factors were chosen as determinants. Statistic data was drawn from annual statistic on communications, yearly statistics GUS and demographic yearly 1967 - 1968. The first chapter defines the connection between postal dispatches, letters & parcels, and socio-economic factors. We note the greatest value of partial correlation coefficients for fundamental postal services with such variables as: saving accounts per resident in thousand zlotys (+ 0,7319), consumption of material goods from private incomes per inhabitant in thousand zlotys (—0.5938), employment in municipal and domestic economy per 1000 inhabitant (+0.8107) employment in education, science and culture (+0.6968). The second chapter defines the connection between subscribers: private telephones, trunk calls, and socio-economic factors. We note the greates valute for the pertial correlation coefficient for fundamental telecommunication services with such variables as: sales in State retail trade per inhabitant in thousand zlotys (+0.7281), saving accounts per inhabitant in thousand zlotys (+0.5429), employment in municipal and domestic economy per 1000 inhabitants (0.8429). Hence the socio-economic factors are accepted as being adaptable in anticipating extrapolation.
Socio-economic Determinants of Demand in Postal-Telecommunication Services